The effect of pendulum training on developing some special physical abilities and offensive handball skills for Athletes - Hadi Jasim , Mohamed; Saeed, Wajdi Majeed; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to investigate the facts of pendulum training and its role in developing the level of physical capabilities and the level of offensive skill performance of handball game, and the delivery of scientific training information to the coaches of this game about the role of this training and what achieve future results. The research aimed to identify the effect of pendulum training in developing some special physical abilities and offensive handball skills for athletes. The most important conclusions were in the effectiveness of the exercises used and applied in the pendulum training method has helped to develop some unique physical capabilities and attacking handball skills for the athletes. The researcher recommended adadapting the exercises used and applied in the pendulum training method, as it works to develop some special physical abilities and offensive handball skills for the athletes.